Chairman's report: African Elephant Specialist Group / Rapport de la Presidente: Groupe de specialistes de l'elephant Africain - Holly Dublin (Pachyderm)
Notes reports of renewed poaching in central and eastern Africa, the publication of the updated African Elephant Database and the feasibility of disseminating the data in digital as well as written form, the work of the Secretariat towards the upcomimg meeting Range State Dialogue Meeting in Senegal and the work of the Programme officer for west and central Africa.